Analisis Kualitas Pelayanan Pada Program Ayo Sinau Bareng Arek Suroboyo (ASBAS) Oleh Dinas Pendidikan Kota Surabaya (Studi Kasus Program Asbas di Balai Rw 9 Kebraon Kecamatan Karangpilang - Wisnu Adiyatma; Trenda Aktiva Oktariyanda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
At the end of 2022, The Surabaya City Government through the Surabaya education Department launched a program, namely Ayo Sinau Bareng Arek Suroboyo (ASBAS). The ASBAS program aims to provide school - age children with chaperoned assistance and to teach students and teachers to remain conscious of the education conditions in the surabaya city. However, in the process of passing the program, problems such as absences tutors, the presence of children as learners is increasingly declining. The purpose of this study was to learn how well the quality of the services associated with the asbas program by the surabaya city education service. In this study the method is descriptive with a qualitative approach. Data collection techniques used include observation, interviews, and documentation. The study also uses data analysis techniques by gathering data, data reduction, data presentation and data conclusion. In this study, focusing on the theories offered by Sutikno and Arha (2018) about the quality of service: 1) reliability, 2) responsiveness, 3) confidence, 4) emphaty, 5) tangible. First, alternate dimensions contain two indicators, which are about being friendly and ready to help and about being punctual. Second, responsiveness contains two indicators of prompt response and the treatment of complaints that occur when the asbas program walks. A third, confidence factor that displays an indicator of the ability to understand and courtesy of the teachers and a degree of public trust in the asbas program. Fourth, emphaty dimensions strike two indicators of mindfulness demonstrated by the tutors and the teachers willingness to overcome the participants' difficulties. And fifth, alternate dimensions that contain two indicators of the means and infrastructure and the surrounding conditions of the tutors in each region. The recommendations advice that author can give is that of monitoring the program and punishment systems for tutors..